DAMPAK PEMBELAJARAN KONSEP ILMU DASAR MENGGUNAKAN PENDEKATAN ETHNO-SETSAR TERHADAP PENINGKATAN KETERAMPILAN KOMUNIKASI CALON GURU - M Jhoni; M. Hasbi; Winarto Winarto (Postgraduate, University of Mataram, 2023)
Communication skills really need to be provided to prospective teachers. Success This research aims to analyze the impact of Ethno-SETSaR science learning on prospective teacher communication. The research method used was an experiment with a non-equivalent group design. The sample of this research is 120 prospective teacher students. The data collection technique used is observation. The data analysis technique used is ANOVA. Hypothesis testing is that there are differences in communication skills between the experimental group and the control group. The research results obtained by the science learning program using the E-SETSAR approach can improve communication skills. Eight student communication indicators with scores greater than â‰¥ 65 for the experimental class. Conduct investigations, prepare investigation reports, discussions and presentations which are learning activities. Learning basic science concepts involves scientific investigation activities to find community problems related to the culture of the surrounding community to be studied from the SETSaR aspect to train communication skills. Therefore, learning is designed to facilitate students to think and convey their ideas.